The Effect of Low Dosage MSC-Conditioned Medium on Urea Levels in Acute Renal Failure - Istania, Rizqi Windhu Sri; Kustyah, Azizah Retno; Sa'dyah, Nur Anna Chalimah (Stem Cell and Cancer Research (SCCR), 2022)
Background: Acute renal failure (ARF) is still associated with a high incidence of morbidity and mortality, as well as a high risk of developing chronic renal failure. ARF is a major public health problem, it is associated with high mortality, morbidity, and long-term risk of chronic kidney disease. One of the assessments of kidney function is the increase in serum urea in the body. The kidneys have an extraordinary ability to regenerate after injury and fully recover, and clinical options are limited to fluid management and dialysis procedures. The development of new strategies in order to increase the ability of kidney regeneration due to ARF, and to maintain kidney function both in the short term and in the long term is needed. This study aims to determine the effect of low-dose MSC-CM on urea levels in ARF. Method: This research is an in vivo research with the type of research Post Test Only Control Group Design. This study used a model of acute renal failure by inducing gentamicin and used 2 research groups, namely the control group (PBS), and the treatment group (MSC-CM 0.2. urea was examined using a spectrophotometer and then analyzed by unpaired t-test. Result: The results of this study showed that the mean urea levels between the control group (19.46 ± 0.56 mg / dL) and the treatment group (13.96 ± 0.73 mg / dL) were significantly different (p <0.05). Conclusion: The conclusion of this study indicated that there was an effect of low-dose of MSC-CM on urea levels in acute renal failure.